FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN WISATAWAN JEPANG TERHADAP JASA GARUDA INDONESIA PADA RUTE PENERBANGAN LANGSUNG JEPANG-BALI - I Made Sudjana (Jurnal Ilmiah Hospitality Management, 2015)
Japan Tourist is one of the four top rank visitors contributes foreign tourists arrival to Bali Island period of year 2011 to 2014, which majority of them carried by Garuda Indonesia aircraft. Garuda Indonesia served direct flight routes to/from Denpasar-Narita (Tokyo), Depasar-Haneda (Tokyo), and Denpasar-Osaka. The purpose of this research is to explore the service performances, factors influenced service quality, effect of service quality toward customers satisfaction, and the important level of each service attribute of Garuda Indonesia aircraft at direct flight route Japan – Bali. The anylisis result used multy regression method by ANOVA Program summarized that there were three (3) class of service level performances classified from 16 service attibutes provide by Garuda Indonesia to its passengers. The first is good level of service performance which consist of two service attributes, the second is neutral/fair level of service performance which consist of twelve (12) service attributes, and the last is poor level of service performance which consist of two (2) service attributes. There were five (5) factors influenced Japan Tourist satisfaction towards Garuda Indonesia service performances on Japan – Bali direct flight route, such as : 1) Technical factor; 2) Tangibles factor; 3) Responsiveness factor; 4) Images factors; and 5) Assurance factor. Meanwhile two factors didn’t influenced Japan Tourist satisfaction, such as Reliability factor and Emphaty factor. This research summarized the rank of  important level (from very important to less important) as follows : Assurance, Technical, Reliability, Responsiveness, Tangible, Empathy, Images.